Co-Designing and Implementing end-to-end Solutions to Meet Farmer's Complex Needs: a science-business approach to scaling climate-smart solutions - Kyere, Reginald (2024)
Private sector businesses provides unique platforms to reach farmers with climate smart solutions. In Ghana, CGIAR partners and national partners are collaborating with Small and Medium Scale Enterprise to co-design and scale bundled products and services that integrate Climate Information Services, Climate Smart Agriculture technologies, information access, market access, credit finance, insurance and digital tools.